INDEKS HARGA SAHAM PROPERTI TERHADAP INDIKATOR MAKRO EKONOMI - Dhea Zatira; Titis Nistia Sari (Universitas Muhammadiyah Tangerang, 2019)
This study aims to examine the effect of the BI Rate, Inflation and Exchange Rate on the stock price index of properti, real estate and building construction companies listed on the Indonesia Stock Exchange in the period January 2016 to June 2019. The data analysis technique used in this study is a model simple regression. The test results prove that the BI Rate (X1) has no effect on the IHSP with the value of t-statistic -1.087355 <t-table 2.02439 and probability value 0.2837> 0.05. Inflation (X2) has a negatif effect on the IHSP with the t-statistic value -4.274569> t-table 2.02439 and a probability value of 0.0001 <0.05. The exchange rate has a negatif effect on the IHSP with the value of t-statistic 11.99475> t-table 2.02439 and the probability value of 0.0000 <0.05. to find out the effect together, the F test is used in which the results of the BI Rate, Inflation and Exchange Rate simultaneously influence the IHSP which is indicated by Ftable of 2.85 and the F-statistic probability value of 0.0000 <0.05, with the magnitude of simultaneous influence of 81.1016% can be seen from the Rsquared value. While the remaining 18,898% is explained by other variables not examined. Keywords: BI Rate, Inflasi, Kurs dan IHSP